2015
DOI: 10.1007/s12630-015-0457-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of palonosetron for preventing postoperative nausea and vomiting: a systematic review and meta-analysis

Abstract: Purpose Palonosetron, a second-generation 5-hydroxytryptamine 3 receptor antagonist (5-HT 3 RA), has unique characteristics relative to first-generation 5-HT 3 RAs such as ondansetron. Nevertheless, it remains unclear if palonosetron is better than ondansetron for the prevention of nausea and vomiting during the first 24 hr after surgery and is thus the focus of this systematic review. RésuméObjectif Le palonosétron est un antagoniste du récepteur de la 5-hydroxytryptamine 3 (5-HT 3 RA) de deuxième génération… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…Our study also correlates well with a systemic review and meta-analysis by Xiong et al . [ 16 ] for comparison of palonosetron and ondansetron for prevention of PONV within 24 hours after surgery. Their primary outcomes were postoperative nausea, postoperative vomiting, or both in early (0–6 hours) or late (0–24 hours) postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also correlates well with a systemic review and meta-analysis by Xiong et al . [ 16 ] for comparison of palonosetron and ondansetron for prevention of PONV within 24 hours after surgery. Their primary outcomes were postoperative nausea, postoperative vomiting, or both in early (0–6 hours) or late (0–24 hours) postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…There have been recent previous meta-analyses comparing either palonosetron4 or ramosetron323 with ondansetron, but a direct comparison between each other has not yet been made. Xiong, et al4 reported that palonosetron provides better prophylaxis against early PON (0–6 hr), late PON (6–24 hr), and late POV (6–24 hr), compared to ondansetron.…”
Section: Discussionmentioning
confidence: 99%
“…Xiong, et al4 reported that palonosetron provides better prophylaxis against early PON (0–6 hr), late PON (6–24 hr), and late POV (6–24 hr), compared to ondansetron. However, this analysis did not provide data for time periods after 24 hrs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations